Performance Evaluation of Sliding Mode Control (SMC) for DC Motor Speed Control - Dimas Dwika Saputra; Alfian Ma'arif; Hari Maghfiroh; Muhammad Ahmad Baballe; Angelo Marcelo Tusset; Abdel-Nasser Sharkawy; Rania Majdoubi (Universitas Ahmad Dahlan, 2023)
DC motor is an industrial motor that is practical for many applications and implementations. However, the speed of a DC motor often decreases because of the given load, thus causing it to be unstable and inconstant. In addition, parameter uncertainty is another issue of DC motors. The performance of the system will be impacted by the uncertainty. Therefore, in this study, SMC is used as speed control of the DC motor since it can handle non-linear plants. The performance also compares with PID to know the effectiveness of the SMC method in DC motor speed control. This study proposes a hardware design and implementation of DC motor angular speed control on Arduino UNO as an embedded control system. The performance comparison analysis results proved that both controllers could perform well. However, both controllers need further fine-tuning. There are still overshoot and steady-state errors for PID and SMC, respectively. In future work, the optimization method can be used to find the optimal gain or by combining it with an adaptive algorithm.